2006
DOI: 10.1182/blood-2005-11-4388
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of a functional human immune system in immunodeficient mice through combined human fetal thymus/liver and CD34+ cell transplantation

Abstract: IntroductionHuman hematopoietic tissue and cell transplantation into immunodeficient mice, such as mice with the severe combined immunodeficiency (SCID) 1,2 mutation and their derivatives, including NOD/SCID, 3 NOD/SCID/␤2m null , 4 and NOD/SCID/ ␥c null mice, 5 has been widely used to study the function of human immune cells. However, only a few studies have shown the ability to achieve systemic in vivo immune responses in humanized mice. 6 In general, immunodeficient mice that received a transplant of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
437
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 415 publications
(458 citation statements)
references
References 30 publications
13
437
1
1
Order By: Relevance
“…Continued genetic modifications of candidate host mice will probably enable at least some of the species-specific needs to be addressed in the future. These include the possibility of creating transgenic mice that will express species-specific human cytokines, or the use of humanized mice (mice transplanted with human haematopoietic or local tissue components) to create more human-type microenvironments -as has proved useful for certain types of normal human cells [53][54][55][56][57] . Orthotopic injections of CSCs into various target organs may also prove useful, and mimicry of natural tumour immunosurveillance mechanisms may be achievable using injections of specific immune effector cells (TABLE 2).…”
Section: Csc Assays: Strengths and Caveatsmentioning
confidence: 99%
“…Continued genetic modifications of candidate host mice will probably enable at least some of the species-specific needs to be addressed in the future. These include the possibility of creating transgenic mice that will express species-specific human cytokines, or the use of humanized mice (mice transplanted with human haematopoietic or local tissue components) to create more human-type microenvironments -as has proved useful for certain types of normal human cells [53][54][55][56][57] . Orthotopic injections of CSCs into various target organs may also prove useful, and mimicry of natural tumour immunosurveillance mechanisms may be achievable using injections of specific immune effector cells (TABLE 2).…”
Section: Csc Assays: Strengths and Caveatsmentioning
confidence: 99%
“…BLT mice were prepared essentially as previously described (6,11,12,24,25,31,41,45). Briefly, thymus/liver-implanted NOD/SCID or NOD/SCID-gamma chain null mice (NSG) (The Jackson Laboratories) were transplanted with autologous human fetal liver CD34 ϩ cells (Advanced Bioscience Resources) and monitored for human reconstitution in peripheral blood by flow cytometry, as we have previously described (11,12,31,45).…”
Section: Methodsmentioning
confidence: 99%
“…However, this kind of introduction of exogenous TCR gene may lead to mispairing of the endogenous TCR subunits with introduced TCR chain, which may alter the TCR specificity of antigen recognition, not only lead to the loss of antitumor, but also the formation of autoreactive T cells (85)(86)(87). Hu et al (91) have shown the humanized mouse (hu-mouse) model which transplantation of human fetal thymus tissue and CD34 + fetal liver cells into immunodeficient mice, leading to the development of human lymphohematopoietic cells and the formation of secondary lymphoid organs (88)(89)(90). They used this hu-mouse model to generate melanoma antigen (MART-1) specific human T cells for studies of human cancer immunotherapy.…”
Section: Antigen-specific Tcr Gene Transductionmentioning
confidence: 99%